Impact of Liberalization in European Union on Innovativeness and Competitiveness of Polish Services Companies in the Perspective of Research - Szukalski, Stanisław Maciej; Dąbrowska, Anna; Janoś-Kresło, Mirosława; Piotrkowski, Jan (Acta Universitatis Lodziensis. Folia Oeconomica, 2018)
The article presents results of research about Polish services companies. It has been conducted to assess the impact that services liberalization on the EU market has on competitiveness and innovativeness of Polish services companies, which is a result of a EU Services Directive from 2006. The research has been conducted on 400 companies that provide services in such areas: commerce, building, craftsmanship, business specialization, tourism, accommodation services, catering. The idea was to assess how this subject is perceived by the above‑mentioned entities as well as assessment of benefits and barriers that come with the liberalization of services market. Research hypothesis: Services Directive impacts positively the competitiveness and innovativeness of Polish services companies on the EU market and has been positively verified. The article itself is a research.